2021
DOI: 10.2166/wpt.2021.052
|View full text |Cite
|
Sign up to set email alerts
|

Variability of faecal sludge characteristics and its implication for dewaterability across different on-site sanitation containments in unplanned settlements in Dar es Salaam, Tanzania

Abstract: This article evaluates the physical-chemical parameters of Faecal Sludge (FS) as possible predictors of dewatering performances. Also, the variability of FS dewatering characteristics was assessed from different containments and in different seasons in relationship with dewatering performance. A total of 120 samples were analyzed were collected and analyzed during the rainy and dry seasons in April and July 2019, respectively to capture season variability. FS from pit latrine (PT) took longer to dewater follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…The Total solids (TS) and the volatiles solids (VS) significantly increased in the sludge tank and the dry bed, respectively (12.66 ± 0.48% to 53.40±8.82% and 11.22±0.09% to 29.79±9.94%). This increase in the values of TS and VS after dewatering agrees with a study by Douglas et al (2021), where there was a significant increase of TS of sludge samples from pit latrine during the dry season. In addition, al-Malack et al ( 2008) also recorded an increase in the VS from 51, 51 and 53 per cent to 65, 62 and 66 per cent at the sludge tank, lagoons and dry beds respectively.…”
Section: Journal Of Environmental Sciences and Technologysupporting
confidence: 91%
“…The Total solids (TS) and the volatiles solids (VS) significantly increased in the sludge tank and the dry bed, respectively (12.66 ± 0.48% to 53.40±8.82% and 11.22±0.09% to 29.79±9.94%). This increase in the values of TS and VS after dewatering agrees with a study by Douglas et al (2021), where there was a significant increase of TS of sludge samples from pit latrine during the dry season. In addition, al-Malack et al ( 2008) also recorded an increase in the VS from 51, 51 and 53 per cent to 65, 62 and 66 per cent at the sludge tank, lagoons and dry beds respectively.…”
Section: Journal Of Environmental Sciences and Technologysupporting
confidence: 91%
“…Characteristics of fecal sludge in this study are presented in Figure 3. The characterization results (i.e., pH, EC, VS, TS, COD) did not follow a normal distribution (Shapiro-Wilk test < 0.05), as is commonly observed with characteristics of fecal sludge (Gold et al, 2018;Englund et al, 2020;Doglas et al, 2021;Strande et al, 2021). Hence, medians are reported as more representative, or when reporting mean and standard deviation, we also report how far apart the mean and median are.…”
Section: Qualities: Comparison Of Fecal Sludge Characteristics In Sev...mentioning
confidence: 94%
“…Previous studies have found that concentrations of heavy metals in faecal sludge vary based on season and source. For example, a study in Dar es Salaam, Tanzania, found a significant difference between the dry and rainy seasons in conductivity value and total solids concentration in pit latrine sludge (Doglas et al, 2021). Yet, it may be difficult to extrapolate data from African studies to the Asian context.…”
Section: Introductionmentioning
confidence: 99%